Pronunciation Error Made During English Presentation by English Department Students at FKIP UNSULBAR - Asdar; Hustiana; Husnul Khatimah Nur (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Learning a second or foreign language (L2), students ought to be capable in the capabilities. Most of the time, learners of L2 should first learn linguistic competence, which includes knowing how to speak, use words, and grammar. Pronunciation issues, particularly when it comes to articulating diphthong sounds, may be a problem for the majority of undergraduate students. Despite the fact that the lesson was covered in class, some students struggle to pronounce it correctly. The researcher analyzed which pronunciation errors students make when speaking in presentation class, the subsequent research of this study focuses on the analysis of the words that undergraduate students from Universitas Sulawesi Barat pronounce. This study was aimed to examine students' mispronunciation of various English words in recognition of the significance of improving pronunciation. Descriptive methods were used in this study, which took a qualitative approach. The researchers described the outcomes of their data collection using this descriptive approach. Enlightening technique picked by the researcher since this strategy gave a detail image of the individual, the condition of language, side effects or gatherings contemplated. Universitas Sulawesi Barat because the researcher wants to know which pronunciation mistakes students make when speaking in presentation class.  English pronunciation errors pronounced by students such as, presentation (/ˌprez.ənˈteɪ.ʃən/), communication (/kəˌmjuː.nəˈkeɪ.ʃən/), made (/meɪd/). Those words have mispronounce that were made by the students. Besides, there were some difficulties that students had. They were Paucity words, a lack of confidence in pronunciation, never practice, lack of English grammar and others.